Menanamkan Nilai-nilai Karakter pada Anak Melalui Kisah Nabi Nuh as - Mushlih, Ahmad (ACIECE, 2018)
This article discusses the value of the character that should be instilled in children. the charactersare part of the human self as a reflection of life step view of life and religious ideology. Issues ofthe nation from the time to time will not be finished if weak leaders and aides in maintaining apositive outlook on life as a character. Many cases such as corruption, a student Brawl, crimeand so on. This is a reflection of the weak value of the person's character. Thus the cultivation ofthe character value to be given and conditioned since I was a kid. the story becomes one way oflearning for children. through talking with the theme of prophets certainly adds to theunderstanding of the value of the character that is owned by the prophets, in this case, theNoah, as the value of the character that can be emulated from the Prophet Noah., honest,Religious tolerance, discipline, hard work, creative, independent, democratic, curiosity,friendly/communication, peace-loving, caring, social responsibility